Developing Culturally Sensitive Suicide Prevention Programs for Medical Professionals in Indonesia - Ni Made Nova Indriyani; Mischa Chantal Adella; Patricia Wulandari; Despian Januandri (HM Publisher, 2024)
Introduction: Medical professionals in Indonesia experience high levels of stress, increasing their risk for mental health problems and suicidal behavior. Culturally appropriate suicide prevention programs are critical to address this issue. This study aimed to develop and evaluate the feasibility and acceptability of a culturally adapted suicide prevention program for Indonesian medical professionals. Methods: This mixed-methods study had two phases. Phase 1 involved program development, adapting an existing evidence-based suicide prevention program using a Delphi method with Indonesian mental health experts (n=10) and cultural consultants (n=5). Phase 2 comprised a pilot implementation of the program with 30 medical professionals. Quantitative data on program feasibility (attendance, completion rates) and acceptability (satisfaction surveys, qualitative feedback) were collected and analyzed. Results: The Delphi method resulted in a culturally adapted program incorporating Indonesian values related to collectivism, family support, religious beliefs, and stigma associated with mental health. Pilot implementation showed high attendance (87%) and program completion rates (93%). Participants expressed high satisfaction with the program's content, cultural relevance, and delivery format. Qualitative feedback emphasized the importance of peer support, spiritual integration, and addressing workplace stressors. Conclusion: This study provides preliminary evidence for the feasibility and acceptability of a culturally sensitive suicide prevention program for Indonesian medical professionals. Further research is needed to evaluate the program's effectiveness in reducing suicidal ideation and behavior.